2000
DOI: 10.3998/ark.5550190.0001.324
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor imidazotetrazines. 38. New 8-substituted derivatives of the imidazo[5,1-d]-1,2,3,5-tetrazines temozolomide and mitozolomide

Abstract: The imidazo[5,1-d]-1,2,3,5-tetrazine ring-system is hypersensitive to attack by nucleophiles. Therefore, acidic conditions were applied successfully to synthesise new 8-substituted derivatives of the antitumor agents temozolomide (1a) and mitozolomide (1b). The 8-cyanoimidazotetrazines (7a, b) were prepared by dehydration of temozolomide and mitozolomide with thionyl chloride and 7b was converted to the corresponding 8-thioamide (9) with thioacetamide in DMF-HCl. Generation of tertiary carbocations from substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…A variety of TMZ derivatives has been previously reported (1317, 2328). The most common modification sites for these analogs are at the N3 or C8 positions of TMZ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of TMZ derivatives has been previously reported (1317, 2328). The most common modification sites for these analogs are at the N3 or C8 positions of TMZ.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, NEO212 is a covalent bond of perillyl alcohol to the C8 site of TMZ, thereby enhancing the efficacy of TMZ (2527), while TMZ hexyl ester which incorporates a hexyl ester bound to the C8 site of TMZ can improve TMZ skin delivery and antitumor potency (28). In addition, other C8-substituted derivatives such as 8-cyano-imidazotetrazine and 8-thiotemozolomide have been developed, but their antitumor mechanism(s) remain to be defined (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early phase of work on imidazotetrazines, the synthesis of a range of derivatives of MTZ, modified at the 8-position was carried out, and their growth-inhibitory activities were evaluated against murine tumors in vitro and in vivo, including leukemias P388 and L1210 and the TLX5 lymphoma. [6][7][8][9] Overall, it was concluded that a substituent at C-8 with a weakly acidic amide NH atom was apparently required for good inhibitory activity. Thus, although the parent carboxylic acid 4 (pK a ~3 ) was poorly active, high potency was recorded for MTZ 2 itself (NH pK a ~1 5), a range of N-alkyl-and -aryl carboxamides NH such as 5 and 6 (NH pK a ~1 1-14), hydroxamic acid 8, sulfonamide 9 (NH pK a ~9 ), and N-methylsulfonamide 10 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] It is hypothesised that modications at position 8 could play a role in: modifying the transport properties of the drug; disturbing the interactions between the inactive prodrug and the DNA; or exerting kinetic control of the hydrolytic degradation of the prodrug. 15,20 In the present study, a series of position 8 modied ester and amide analogues of TMZ were synthesised, with the aim of increasing the activity. The modied analogues could provide the foundations for potential alternatives to TMZ that possess superior chemotherapeutic activity for the treatment of GBM.…”
Section: Introductionmentioning
confidence: 99%